A comprehensive evaluation of the logistics service quality based on vague sets theory. (1st January 2014) - Wu, Ai-Hua; Su, Jing-Qin; Wang, Fei
The main purpose of the study is to establish a method for evaluating the logistics service quality. Some studies have applied the SERVQUAL to evaluate service quality, however most of these studies focus on the choice of index, and the evaluation method of logistics service quality receives little attention, especially fuzzy evaluation method. As a fact human judgments are often vague and it is not easy to express the weights of evaluation criteria and the satisfaction of logistics service quality with an exact numerical value. Due to the existing fuzziness in the logistics service quality evaluation and a vague set can provide more information than a fuzzy set, vague set theory is an appropriate method for dealing with uncertainty. This article attempts to fill this gap in the current literature by establishing an improved fuzzy comprehensive evaluation method based on vague sets for evaluating the logistics service quality. The method may reflect both for/true and against/false judgment information in practice and it will efficiently manage the essential fuzziness in human judgment and preference. Moreover, an example of the evaluation process of logistics service quality is shown to illustrate the proposed theory and method.